Positional group significantly influences the offensive and defensive skill involvements of junior representative rugby league players during match play - Bennett, K. J. M.; Fransen, J.; Scott, B. R.; Sanctuary, C. E.; Gabbett, T. J.; Dascombe, B. J. (Journal of Sports Sciences, 2016)
This study examined the skill involvements of three positional groups across a junior representative rugby league season. Data were collected from 45 rugby league players (mean ± SD; age = 16.5 ± 1.0 years) currently participating in the Harold Matthews and SG Ball Cup. Players were subdivided into hit-up forwards, adjustables and outside backs. The frequency (n/min) of offensive, defensive and overall involvements was coded for each group using a notation system and a practical coach skill analysis tool. Multivariate analysis of variance (MANOVA) revealed a significant effect of playing position on skill involvements (F = 9.06; P < 0.001; ES = 0.41). Hit-up forwards performed a significantly greater frequency of offensive (0.31 ± 0.10), defensive (0.42 ± 0.15) and overall involvements (0.74 ± 0.19) when compared to adjustables (0.20 ± 0.08, 0.28 ± 0.08 and 0.52 ± 0.15, respectively) and outside backs (0.20 ± 0.12, 0.11 ± 0.07 and ± 0.31 ± 0.17, respectively). Further, adjustables performed a significantly greater number of defensive (0.28 ± 0.08) and overall involvements (0.52 ± 0.15) when compared to outside backs (0.11 ± 0.07 and 0.31 ± 0.17, respectively). The findings of this study suggest that it is important to consider a junior player`s positional group when analysing their skill involvements. Information gained from this study could assist in the design of specific training methodologies for junior rugby league players in high-level talent development programmes.